2021
DOI: 10.1007/s12539-021-00463-2
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Covid-19 with Bidirectional LSTM Network Using Deep Features Extracted from Chest X-ray Images

Abstract: Coronavirus disease, which comes up in China at the end of 2019 and showed different symptoms in people infected, affected millions of people. Computer-aided expert systems are needed due to the inadequacy of the reverse transcription-polymerase chain reaction kit, which is widely used in the diagnosis of this disease. Undoubtedly, expert systems that provide effective solutions to many problems will be very useful in the detection of Covid-19 disease, especially when unskilled personnel and financial deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Another contribution in [ 15 ] developed a DL model based on Convolutional Neural Networks (CNNs) combined with Transfer Learning to predict COVID-19 from chest X-rays accurately. Furthermore, the Bidirectional LSTM network is also widely used in research; the authors in [ 16 ] also proposed ML approaches in detecting COVID-19 by chest X-ray images. They showed that the classification performance of the Bi-LSTM network on in-depth features gives the best results.…”
Section: Related Workmentioning
confidence: 99%
“…Another contribution in [ 15 ] developed a DL model based on Convolutional Neural Networks (CNNs) combined with Transfer Learning to predict COVID-19 from chest X-rays accurately. Furthermore, the Bidirectional LSTM network is also widely used in research; the authors in [ 16 ] also proposed ML approaches in detecting COVID-19 by chest X-ray images. They showed that the classification performance of the Bi-LSTM network on in-depth features gives the best results.…”
Section: Related Workmentioning
confidence: 99%
“…A new method for identifying COVID-19 using X-ray images is proposed. Bi-LSTM network on the deep features [72] The study proposes a deep learning-based method for detecting Covid-19 and undetected cases using chest X-rays. Despite the small number of Covid-19 images in the dataset, the Bi-LSTM network outperformed the deep-neural net (DNN) with an accuracy of 97.6%.…”
Section: Classic Teleconsultation Model [30]mentioning
confidence: 99%
“…These approaches are useful for doctors performing diagnosis and therapy. Keymal and Şen used automatic detection with a bidirectional LSTM network and deep features [8]. They relied on the Bi-LSTM network inside the deep feature and then compared it with the deep neural network of the fivefold cross-validation approach.…”
Section: Motivation Of Studymentioning
confidence: 99%
“…Their model was trained using 100 epochs and 32 batch sizes. The fourth section of their model was designed to handle the activation function, with two neurons representing the classes COVID-19 and no-finding [8]. A radiological study found a diagnostic tool for COVID-19.…”
Section: Motivation Of Studymentioning
confidence: 99%